Pelayanan Sertifikasi Halal Produk Non Daging bagi Pelaku UMKM di MUI Kabupaten Purwakarta - Muzzamil, Faisal; Basyariyyah, Riri Khoeriyyatul; Hasanah, Haula Laelatul; Agnia, Syifa Fricilla; Rodiah (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
The Community Service (PKM) activity in the form of Halal certification services for non-meat products for MSMEs at the Purwakarta Indonesian Ulema Council (MUI) was motivated by the main problem of hoax news about the making of Halal certification. Based on this background, in general, this PKM activity aims to help and facilitate Micro, Small and Medium Enterprises (UMKM) in the process of submitting Halal certification for non-meat products. Then specifically, there are two objectives of implementing this PKM activity, namely: First, to find out the stages of Halal certification services for non-meat products for Micro, Small and Medium Enterprises (UMKM) at the Purwakarta Regency Indonesian Ulema Council (MUI); Second, to assist the process of Halal certification services for non-meat products for MSMEs at the Purwakarta Regency MUI. Based on the results of the implementation of the PKM activity, two strategic findings were obtained in this PKM activity, namely: First, there are three stages of service carried out in submitting Halal certification for non-meat products at the Purwakarta MUI, namely: (1) Document Preparation Stage; (2) Document Collection Stage; (3) Document Upload Stage. Second, there are three forms of service in the Halal certification process for non-meat products at MUI Purwakarta, namely: (1) Service in the Documentation Process; (2) Service in the Verification Process; (3) Service in the Registration Process. The results of this PKM activity can be useful and contribute to the following two aspects: (1) Theoretically, this PKM activity is useful for increasing students' insight and skills in the field of community service, especially Halal certification services and assistance; (2) Practically, this PKM activity is useful for helping and facilitating UMKM actors in the process of applying for Halal certificates for their products, especially non-meat products.